Comparison between upper thoracic spine mobilization and the Ergon technique in the treatment of mechanical neck pain - Hebatalla M. Said Zaghloul; Shahesta A. Osama Ghally; Mona M. Talaat Abdelkhalek; Marwa T. Mohamed; Lama S. El-Din Mahmoud; Lamis A. Osama Ghaly (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.